Pengaruh Work Life Balance Dan Fleksibilitas Terhadap Kepuasan Kerja Karyawan Sea Today - Salwa, Nailah; Lahat, Mohammad Amas; Utama, Dani Chandra (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
The post-pandemic transformation of the workplace has elevated employee well-being to a strategic priority, where the concepts of work-life balance and work flexibility have become key to retaining talent, especially from the Millennial and Gen Z generations. In line with this, a quantitative study, using a survey distributed via Google Form to 52 employees at Sea Today located at STO Telkom Gambir, Central Jakarta, aimed to analyze the influence of these two factors on job satisfaction. The research findings proved the proposed hypotheses: first, work-life balance has a partially positive and significant effect on job satisfaction, as evidenced by a t-test showing a t-statistic of 9.915, which is greater than the t-table value of 1.675, and a significance level of 0.000 < 0.05. Second, work flexibility also demonstrates a partially positive and significant influence, with a t-statistic of 10.000, which also exceeds the t-table value of 1.675, with a significance of 0.000. Even more significantly, when tested simultaneously, these two variables together have a very strong impact on job satisfaction, as indicated by the F-test results, which show an F-statistic of 112.002, far exceeding the F-table value of 3.18, at a significance level of 0.000. Thus, it can be firmly concluded that companies implementing policies that support work-life balance and provide effective work flexibility will create a highly satisfying environment for employees, which in turn maximizes the quality of human resources to achieve company goals efficiently.